2012
DOI: 10.1186/1477-7819-10-160
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor gene RBM5 inhibits lung adenocarcinoma cell growth and induces apoptosis

Abstract: BackgroundThe loss of tumor suppressor gene (TSG) function is a critical step in the pathogenesis of human lung cancer. RBM5 (RNA-binding motif protein 5, also named H37/LUCA-15) gene from chromosome 3p21.3 demonstrated tumor suppressor activity. However, the role of RBM5 played in the occurrence and development of lung cancer is still not well understood.MethodPaired non-tumor and tumor tissues were obtained from 30 adenocarcinomas. The expression of RBM5 mRNA and protein was examined by RT-PCR and Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Additionally, underexpression of RBM5 had a close association with unfavorable clinicopathological features, including lymph node metastasis, distant metastasis, advanced UICC stage and presence of nerve and venous invasion, suggesting its potential role in tumor invasion and progression. Several studies have showed that RBM5 is differentially expressed in human cancers and is involved in tumorigenesis (1518). Oh et al (19) found that the tumor suppressor RBM5/H37 alters the expression of genes involved in metastasis, suggesting that a loss of RBM5 expression may increase the metastatic potential of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, underexpression of RBM5 had a close association with unfavorable clinicopathological features, including lymph node metastasis, distant metastasis, advanced UICC stage and presence of nerve and venous invasion, suggesting its potential role in tumor invasion and progression. Several studies have showed that RBM5 is differentially expressed in human cancers and is involved in tumorigenesis (1518). Oh et al (19) found that the tumor suppressor RBM5/H37 alters the expression of genes involved in metastasis, suggesting that a loss of RBM5 expression may increase the metastatic potential of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the disorders annotated for human genes in malacards, 165 were found to be highly enriched for RBPs (p<1e-05, FDR<1% and number of annotated RBPs >10) which included all major types of cancers -breast, lung, prostate and liver as well as neurodegenerative diseasesParkinson's disease and down syndrome ( Figure 5A). For example, genes like ELAV1, which regulate mRNA stability are known to contribute to breast cancer [65], RBM5, a tumor suppressor gene is known to control cell growth in lung cancer [66], UPF1, subunit of the post splicing multi protein complex is shown to be dysregulated in prostate cancer [67]. RBPs that are known to be dysregulated in neurodegenerative diseases include members of the NOVA family [68], QKI, a candidate gene for schizophrenia [69] and ELAVL4, an important player in parkinson's disease [70].…”
Section: Rbps Are Significantly Associated With Inflammatory Diseasesmentioning
confidence: 99%
“…In regards to lung cancer specifically, some functional work regarding RBM5 has been performed using a lung adenocarcinoma cell line (A549), which showed that increased RBM5 expression correlated with (a) G 1 cell cycle arrest (Network, 2014; Shao et al, 2012), and (b) increased apoptosis (Oh et al, 2006; Shao et al, 2012). No functional work, however, has been undertaken for RBM5 in SCLC.…”
Section: Introductionmentioning
confidence: 99%